Comparison of Early Versus Late Removal of Foley’s Catheter in Patients After Transurethral Resection of Prostate - Javed, Muhammad; Rasool, Mumtaz; Barkat, Burhan; Amjad, Muhammad; Saleem, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
The primary surgical intervention addressing urinary blockage caused by an enlarged non-cancerous prostate involves a procedure performed via the urethra. Despite its widespread use, protocols for the timing of catheter withdrawal after surgery differ significantly. This research aimed to evaluate outcomes between patients undergoing immediate versus postponed catheter extraction, analyzing factors such as hospitalization duration, volume of tissue excised during the procedure, operative time, need for blood transfusions during or after surgery, and adverse events following the intervention. Methods: This prospective clinical investigation was conducted at the Department of Urology, Victoria Hospital, Bahawalpur, from 25th December 2024 to 25th March 2025. Patients were chosen through a random selection methodology following consent authorization and categorized into two groups: Group A-standard catheter removal group, and Group B-early catheter removal group. Exclusion criteria comprised individuals with elevated residual urinary retention, concurrent urethral procedures alongside prostate tissue excision, underlying medical conditions, and surgical challenges during the operation. Patients were cleared for discharge post-catheter extraction contingent on demonstrating proper urination. In Group A, drainage tubes were retained beyond 24 hours per established guidelines. The data were analyzed using SPSS-17. Results: The study was conducted with 320 patients, 163 in Group A and 157 in Group B. The average mass of excised tissue in Group A was 46.67±9.133 grams; it was 45.22±7.532 grams in Group B. The Mean catheter removal day was 4.13±1.65days in Group A and 1.23±0.933 days in Group B. Hospitalization periods differed markedly, with Group A averaging 3.57 days±1.028 and 1.29 days±1.030 in Group B (p-value<0.05). A direct relationship was observed between hospitalization duration and the timing of catheter extraction. Both groups demonstrated comparable rates of post-surgical adverse events, with no notable discrepancy in clinical outcomes. Conclusion: Removal of the catheter on the first postoperative day after transurethral prostatectomy does not heighten the likelihood of post-surgical adverse effects and is correlated with reduced hospitalization duration.